Two new species of nereidids (Annelida, Polychaeta) from Taiwan - Hsueh, Pan-Wen (Zootaxa, 2019)
Two new species of nereidids, Dendronereis chipolini n. sp. and Neanthes hsinchuensis n. sp., collected from brackish aquaculture ponds near coasts of southern Taiwan and fouling community on docks of the Hsinchu fishing port in northwestern Taiwan, respectively, are described in the present study. Dendronereis chipolini n. sp. differs from its congeners by a combination of number and morphology of branchiae, morphology of neuropodia and form of neuropodial homogomph spinigers. Neanthes hsinchuensis n. sp. can be distinguished from congeners reported from East and Southeast Asia by a combination of numbers of conical paragnaths, morphology of notopodia, the absent/present of prechaetal lobe and forms of neuropodial chaetae. A key to Dendronereis species of the world is included, together with a table of morphological characters of Neanthes species reported from East and Southeast Asia, which have no conical paragnaths on Area V of the pharynx.